2020
DOI: 10.1146/annurev-psych-122216-011613
|View full text |Cite
|
Sign up to set email alerts
|

Depression's Unholy Trinity: Dysregulated Stress, Immunity, and the Microbiome

Abstract: Depression remains one of the most prevalent psychiatric disorders, with many patients not responding adequately to available treatments. Chronic or early-life stress is one of the key risk factors for depression. In addition, a growing body of data implicates chronic inflammation as a major player in depression pathogenesis. More recently, the gut microbiota has emerged as an important regulator of brain and behavior and also has been linked to depression. However, how this holy trinity of risk factors intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
161
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(168 citation statements)
references
References 219 publications
(210 reference statements)
2
161
0
5
Order By: Relevance
“…Despite the effect of sunlight inside houses is not currently known it is possible that play a similar role as in the environment, neutralizing virus particles by UV radiation. Additionally, a sunny house represents a key element in preventing depression (An et al 2016;Fleming et al 2018) reinforcing the immune system (Szałach et al 2019;Cruz-Pereira et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the effect of sunlight inside houses is not currently known it is possible that play a similar role as in the environment, neutralizing virus particles by UV radiation. Additionally, a sunny house represents a key element in preventing depression (An et al 2016;Fleming et al 2018) reinforcing the immune system (Szałach et al 2019;Cruz-Pereira et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that the intestinal microbiota plays a significant role in modulating human health and behavior [see comprehensive reviews (Sherwin et al, 2018;Pereira et al, 2019;Zmora et al, 2019)]. Several studies have demonstrated that the human intestinal microbiota is seeded before birth (Stinson et al, 2019), and the mode of delivery influences the composition of the gut microbiota (Ferretti et al, 2018;Shao et al, 2019).…”
Section: Current Knowledge: Gut Microbiota and Human Healthmentioning
confidence: 99%
“…There is also substantial overlap between both classical and more recent neurobiological theories of depression with the impact of our gut microbiota on host physiology, particularly when viewed through the lens of microbial regulation of gut-brain axis signaling. Within this framework, the gut microbiota primes the host stress response [11], plays a role in educating the immune system [12] and has important implications for host tryptophan metabolism and serotonergic neurotransmission [13]. The consequences of growing up germ-free, as well as the impact of more moderate microbiota-based manipulations, is visible at a structural and functional level in key brain regions implicated in depression such as the hippocampus, amygdala and prefrontal cortex [14,15].…”
Section: A River Runs Through It: the Gut Microbiome Brain Function mentioning
confidence: 99%
“…It is worth considering a twin track approach to drive this research forward. Exploiting the strain-specific biological effects of specific candidate psychobiotic bacteria should make it possible to target specific facets of host physiology and in the case of depression, valid targets include the subset of patients with an activated immune system, stress axis hyperactivity or alterations in tryptophan metabolism [12,38]. There is growing interest within the field of psychiatry in matching interventions with specific mechanisms of action to the underlying neurobiology of specific patient populations with one example being immunomodulation [39].…”
Section: Perspectives: What Lies On the Horizon And How Do We Get There?mentioning
confidence: 99%